2016
DOI: 10.1177/0969776415587122
|View full text |Cite
|
Sign up to set email alerts
|

Local and transnational networking among female immigrant entrepreneurs in peripheral rural contexts: Perspectives on Russians in Finnmark, Norway

Abstract: Social networks are vital to the start-up and development of new businesses. In immigrant entrepreneurship research, the key role of co-ethnic networks has been particularly highlighted. However, there is a lack of knowledge about the networking practices of immigrants who start businesses in a rural context where co-ethnic communities do not exist. In order to address this gap, this article highlights the experiences of female Russian immigrant entrepreneurs living in Finnmark in northernmost Norway. Finnmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 71 publications
0
25
0
5
Order By: Relevance
“…The first disadvantage that Yeasmin puts forward is that immigrant entrepreneurs are pushed into entrepreneurship by necessity (Yeasmin, 2016, p. 133). In my study, however, the modes of entry are quite diverse as indicated previously (Munkejord, 2015a). Moreover, even in Yeasmin's study, it is an exaggeration to state that immigrant entrepreneurs in Lapland are 'mainly driven by necessity' as only 10% of her sample reported that they had been pushed to start a business due to unemployment (Yeasmin, 2016, p. 131).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The first disadvantage that Yeasmin puts forward is that immigrant entrepreneurs are pushed into entrepreneurship by necessity (Yeasmin, 2016, p. 133). In my study, however, the modes of entry are quite diverse as indicated previously (Munkejord, 2015a). Moreover, even in Yeasmin's study, it is an exaggeration to state that immigrant entrepreneurs in Lapland are 'mainly driven by necessity' as only 10% of her sample reported that they had been pushed to start a business due to unemployment (Yeasmin, 2016, p. 131).…”
Section: Discussionmentioning
confidence: 61%
“…But, it is a misunderstanding to assume that immigrant entrepreneurs are only interested in serving their ethnic community. Munkejord (2015a) on the contrary reveals that some immigrant entrepreneurs in rural Norway are interested in serving the mainstream marked from day one, and hence that a thin and dispersed immigrant population does not necessarily represent a disadvantage for nascent or operating rural immigrant entrepreneurs. Rather, as this article indicates, the majority population may be interested in supporting immigrant entrepreneurs who settle in sparsely populated areas and their start-up initiatives may be interpreted positively as a contribution to local place development.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gjennom innvandringen får Finnmark mange ressurser i form av personer, kompetanse, kunnskap og nettverk. I Finnmark utgjør russiske migranter den største gruppen innvandrere, og majoriteten av disse er kvinner som har møtt kjaerligheten i fylket (Flemmen and Lotherington 2008, Kramvig and Stien 2002b, Munkejord 2015. De flytter med andre ord over grensen for å bosette seg sammen med en norsk mann.…”
Section: Naturen Som Rekreasjon Og Heteroseksuell Romantikkunclassified
“…Whereas most of the female immigrant entrepreneurs in a broader study of rural immigrant entrepreneurship (Munkejord, 2015a(Munkejord, , 2015bclearly highlighted the importance of spousal support as a motivational or even decisive factor during the start-up phase, few of the male entrepreneurs mentioned this dimension when they discussed their experiences starting their businesses. Also, when I asked them about who had been significant persons in the startup phase, hardly anyone of the participants talked about their wives.…”
Section: Family and Community Supportmentioning
confidence: 99%